2010 ADA standards for accessible design with commentary (BNi Building News, 2012)
"This all-inclusive guide puts both the '2010 ADA standards for accessible design,' which governs the construction and alteration of places of public use, together with the Department of Justice's 'Guidance on 2010 ADA standards for accessible design," in one complete book" -- Cover p. 4.